Solve the following equations and check your results. 1. 8x + 4 = 3 (x – 1) + 7 2. x = 4/5 (x + 10) 3. 2x/3 + 1 = 7x/15 + 3 4. 2y + 5/3 = 26/3 – y 5. 3m = 5m – 8/5
Solve the following equations and check your results.
1. 8x + 4 = 3 (x – 1) + 7
2. x = 4/5 (x + 10)
3. 2x/3 + 1 = 7x/15 + 3
4. 2y + 5/3 = 26/3 – y
5. 3m = 5m – 8/5
1. 8x + 4 = 3 (x – 1) + 7
8x + 4 = 3 (x – 1) + 7
⇒ 8x + 4 = 3x – 3 + 7
⇒ 8x + 4 = 3x + 4
⇒ 8x – 3x = 4 – 4
⇒ 5x = 0
⇒ x = 0
Putting the value of x in RHS and LHS we get,
(8 × 0) + 4 = 3 (0 – 1) + 7
⇒ 0 + 4 = 0 – 3 + 7
⇒ 4 = 4
⇒ LHS = RHS
2. x = 4/5 (x + 10)
x = 4/5 (x + 10)
⇒ x = 4x/5 + 40/5
⇒ x – (4x/5) = 8
⇒ (5x – 4x)/5 = 8
⇒ x = 8 × 5
⇒ x = 40
Putting the value of x in RHS and LHS we get,
40 = 4/5 (40 + 10)
⇒ 40 = 4/5 × 50
⇒ 40 = 200/5
⇒ 40 = 40
⇒ LHS = RHS
3. 2x/3 + 1 = 7x/15 + 3
2x/3 + 1 = 7x/15 + 3
⇒ 2x/3 – 7x/15 = 3 – 1
⇒ (10x – 7x)/15 = 2
⇒ 3x = 2 × 15
⇒ 3x = 30
⇒ x = 30/3
⇒ x = 10
Putting the value of x in RHS and LHS we get,
(2 x 10)/3 + 1 = (7 x 10)/15 + 3
⇒ 20/3 + 1 = 70/15 + 3
⇒ 23/3 = 115/15
⇒ 23/3 = 23/3
⇒ LHS = RHS
4. 2y + 5/3 = 26/3 – y
2y + 5/3 = 26/3 – y
⇒ 2y + y = 26/3 – 5/3
⇒ 3y = (26 – 5)/3
⇒ 3y = 21/3
⇒ 3y = 7
⇒ y = 7/3
Putting the value of y in RHS and LHS we get,
⇒ (2 × 7/3) + 5/3 = 26/3 – 7/3
⇒ 14/3 + 5/3 = 26/3 – 7/3
⇒ (14 + 5)/3 = (26 – 7)/3
⇒ 19/3 = 19/3
⇒ LHS = RHS
5. 3m = 5m – 8/5
3m = 5m – 8/5
⇒ 5m – 3m = 8/5
⇒ 2m = 8/5
⇒ 2m × 5 = 8
⇒ 10m = 8
⇒ m = 8/10
⇒ m = 4/5
Putting the value of m in RHS and LHS we get,
⇒ 3 × (4/5) = (5 × 4/5) – 8/5
⇒ 12/5 = 4 – (8/5)
⇒ 12/5 = (20 – 8)/5
⇒ 12/5 = 12/5
⇒ LHS = RHS
-
The denominator of a rational number is greater than its numerator by 8. If the numerator is increased by 17 and the denominator is decreased by 1, the number obtained is 3/2. Find the rational number.
3 years ago
-
The ages of Hari and Harry are in the ratio 5:7. Four years from now the ratio of their ages will be 3:4. Find their present ages.
3 years ago
-
Solve the following equations. 1. (8x – 3)/3x = 2 2. 9x/(7 – 6x) = 15 3. z/(z + 15) = 4/9
3 years ago
-
Solve the following linear equations. 1. m – (m – 1)/2 = 1 – (m – 2)/3 2. 3(t – 3) = 5(2t + 1) 3. 8. 15(y – 4) –2(y – 9) + 5(y + 6) = 0
3 years ago
-
Solve the following linear equations. 1. x/2 – 1/5 = x/3 + 1/4 2. n/2 – 3n/4 + 5n/6 = 21 3. x + 7 – 8x/3 = 17/6 – 5x/2
3 years ago
- 321 Forums
- 27.3 K Topics
- 53.8 K Posts
- 0 Online
- 12.4 K Members